Anticoagulation membrane material structure and medical instrument
By using a multi-strand fiber bundle braided thin film substrate and fluoropolymer anticoagulation coating on the surface of blood-contact medical devices, the problems of complex and poor safety of anticoagulation in the prior art are solved, safe, stable and simple anticoagulation effects are achieved, and endothelialization of the material surface is promoted.
Patent Information
- Application Number
- CN202311236332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-01
AI Technical Summary
When dealing with anticoagulation problems on the surface of blood-contact medical devices, the prior art has problems such as complex process, worrying safety and obvious side effects, making it difficult to achieve safe, stable and simple anticoagulation treatment.
An anticoagulant membrane structure is adopted using a thin film substrate woven from a multi-strand fiber bundle and an anticoagulant coating containing a fluoropolymer. The anticoagulant coating has several holes with a pore size of 0.5 μm to 5.0 μm, covering the surface of the thin film substrate, providing good hydrophobic properties and film forming properties.
It is achieved to avoid blood adhesions when in contact with blood, and to show good anticoagulation properties. At the same time, due to the good film-forming properties of fluoropolymers, the anticoagulation coating is firmly combined with the film substrate and is not easy to fall off. It has good safety and stability, and promotes rapid endothelialization of the material surface and reduces complications.
Smart Images

Figure CN119733117A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical materials, and in particular to an anti-coagulation membrane structure and a medical device comprising the anti-coagulation membrane structure. Background Art
[0002] Blood-contact biomaterials are a type of implantable materials used in clinical practice that have the potential to treat, replace, or enhance tissue function. Medical devices that come into contact with blood in clinical practice are prone to stimulating coagulation mechanisms and forming thrombi during use. Once blood contacts the surface of the device, platelets and fibrinogen adhere to the surface, forming thrombi. Thrombi can easily enter the human body with the blood and block blood vessels, leading to serious illness or even death. Blood-contact implantable or interventional devices and extracorporeal blood circulation equipment have always faced complications such as postoperative infection and thromboembolism in clinical applications. These complications not only affect the life of the device, but more seriously, they can also cause great harm to the patient. Therefore, the formation of thrombi seriously affects the safety of device use, and anticoagulant treatment of the surface of medical devices that come into contact with blood for a long time is very necessary.
[0003] Currently, the primary clinical strategy for addressing these issues is systemic administration of antibiotics and anticoagulants as adjunctive therapy. However, long-term use of these drugs inevitably leads to a range of side effects, such as antibiotic resistance, thrombocytopenia, and even bleeding. However, most reported surface modification methods are complex, require repeated surface pretreatment, involve toxic chemicals, and pose safety concerns.
[0004] Therefore, for those skilled in the art, how to make the anticoagulant treatment safer and the preparation process simpler while ensuring the anticoagulant effect is a technical problem that urgently needs to be solved. Summary of the Invention
[0005] Based on this, the purpose of the present invention is to provide an anti-coagulation membrane structure and medical device to solve the more common material surface coagulation problem in the existing technology, make the anti-coagulation treatment safer and more stable, the preparation process is simpler, and can be flexibly applied to various medical devices.
[0006] To achieve the above objectives, the present invention provides an anticoagulant membrane structure, which includes a film substrate woven from multiple fiber bundles and an anticoagulant coating comprising a fluoropolymer, wherein the anticoagulant coating covers the surface of the film substrate and has a plurality of holes.
[0007] In one embodiment, the diameter of at least some of the holes is 0.5 μm to 5.0 μm.
[0008] In one embodiment, pores with a pore diameter of 2.0 μm to 5.0 μm account for more than 80% of the total number of pores.
[0009] In one embodiment, each fiber bundle is composed of a plurality of fiber filaments, and a sunken space is formed between adjacent fiber filaments. The anticoagulation coating forms a bridging structure on the sunken space, and at least part of the plurality of holes is distributed on the bridging structure.
[0010] In one embodiment, more than 90% of the holes are distributed on the bridging structure.
[0011] In one embodiment, each fiber bundle is composed of a plurality of fiber filaments, the anticoagulation coating covers the surface of the fiber filaments and the gaps between adjacent fiber filaments, and the anticoagulation coating exposes the mesh on the film substrate.
[0012] In one embodiment, the anticoagulation coating has a thickness of 100 nm to 5000 nm.
[0013] In one embodiment, the material contained in the film substrate is one of polyethylene, polypropylene, polyethylene terephthalate, polyester, polyamide, polyetheretherketone, polysulfone, natural fiber, or a combination of multiple thereof.
[0014] In one embodiment, the anticoagulation coating is composed of one or a combination of multiple fluoropolymers.
[0015] In one embodiment, the anti-coagulation coating is composed of a combination of one or more of polyvinylidene fluoride, polyperfluoroethylene propylene, polyvinyl fluoride and polytetrafluoroethylene.
[0016] Based on the same inventive concept, the present invention also provides a medical device provided with any of the above-mentioned anti-coagulation membrane structures.
[0017] The present invention provides an anticoagulant film material structure, which can be used as a coating on a variety of medical devices to enable the medical devices themselves to have anticoagulant functions, and while achieving good anticoagulant effects, make anticoagulant treatment safer and more stable. Specifically, an anticoagulant coating comprising a fluoropolymer is attached to a film substrate formed by weaving multiple fiber bundles. The anticoagulant coating has good hydrophobic properties and can avoid blood adhesion when in contact with blood, thereby exhibiting good anticoagulant properties. At the same time, since the fluoropolymer has good film-forming properties, the anticoagulant coating can be firmly combined with the film substrate and is not easy to fall off, thereby also having good safety and stability. In addition, the hydrophobic surface of the anticoagulant coating comprising a fluoropolymer is itself very suitable for cell attachment, which is conducive to promoting cell crawling and migration on the coating surface, thereby achieving rapid endothelialization of the material surface to effectively reduce complications. This eliminates the need for long-term antibiotic and anticoagulant therapy, thus avoiding the side effects of medication. Furthermore, the preparation of the anticoagulant coating is simpler and safer than surface modification processes, and can be applied to a variety of medical devices, offering greater flexibility. Furthermore, the inclusion of holes in the anticoagulant coating increases the speed and stability of endothelialization.
[0018] Since the medical device provided by the present invention and the anti-coagulation membrane structure provided by the present invention belong to the same inventive concept, the medical device provided by the present invention has all the advantages of the anti-coagulation membrane structure provided by the present invention, so the beneficial effects of the medical device provided by the present invention will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Those skilled in the art will appreciate that the accompanying drawings are provided for a better understanding of the present invention and do not constitute any limitation on the scope of the present invention.
[0020] Figure 1 This is a schematic structural diagram of an anti-coagulation membrane structure according to an embodiment of the present invention;
[0021] Figure 2 is a partial schematic diagram of the structure of a film substrate covered with an anticoagulant coating according to an embodiment of the present invention, which also shows a cross-sectional view of a fiber bundle and the anticoagulant coating on its surface;
[0022] Figure 3 is a schematic cross-sectional view of an anti-coagulation coating with holes according to an embodiment of the present invention;
[0023] Figure 4 is a schematic cross-sectional view of the anti-coagulation coating with holes according to the first embodiment of the present invention;
[0024] Figure 5is a schematic cross-sectional view of the anti-coagulation coating with holes according to the second embodiment of the present invention;
[0025] Figure 6 is a schematic cross-sectional view of the anti-coagulation coating with holes according to the third embodiment of the present invention;
[0026] Figure 7 2 is a schematic cross-sectional view of the anti-coagulation coating with holes according to the fourth embodiment of the present invention. DETAILED DESCRIPTION
[0027] To make the objects, advantages, and features of the present invention more clearly apparent, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the drawings are all in a very simplified form and are not drawn to scale. They are only used to conveniently and clearly assist in illustrating the purposes of the embodiments of the present invention. In addition, the structures shown in the drawings are often part of the actual structure. In particular, different drawings may need to illustrate different focuses and sometimes use different scales.
[0028] As used in the present invention, the singular forms "a", "an" and "the" include plural objects, the term "or" is generally used in a sense including "and / or", the term "several" is generally used in a sense including "at least one", and the term "at least two" is generally used in a sense including "two or more". In addition, the terms "one end" and "the other end" generally refer to two corresponding parts, which not only include endpoints. The terms "installed", "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integrated connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. In addition, as used in the present invention, "one element is disposed on another element" generally only indicates that there is a connection, coupling, cooperation, or transmission relationship between the two elements, and the connection, coupling, cooperation, or transmission between the two elements may be direct or indirect through an intermediate element. It should not be understood as indicating or implying a spatial positional relationship between the two elements. That is, one element can be in any orientation, such as inside, outside, above, below, or to one side of another element, unless the content clearly indicates otherwise. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0029] It is worth noting that the main anticoagulant method currently used in clinical practice is to use anticoagulants based on heparin to inhibit coagulation so that the surgical operation can proceed smoothly. However, for implantation surgeries such as left atrial appendage filling or vascular stents, it is still necessary to take anticoagulants such as warfarin for a long time to inhibit thrombosis, which will inevitably cause a series of side effects. There are also attempts to use surface modification methods for anticoagulant treatment, but there is still no very mature and widely used solution for anticoagulant modification of medical device surfaces. In particular, the chemical properties of most medical material surfaces are relatively stable (inert), and there are very few active groups that can be used for grafting. Therefore, the surface modification of medical materials is greatly limited. There are also studies on the introduction of active groups on the surface of medical materials using methods such as plasma treatment and polyethyleneimine long-chain molecular adhesion, but there are still problems such as low efficiency of introducing active groups, difficulty in handling, and strong toxicity of the reagents used.
[0030] Therefore, the present invention proposes an anti-coagulation membrane material structure to effectively solve the more common material surface coagulation problem in the existing technology, making the anti-coagulation treatment method safer and more stable, the process simpler, and can be flexibly applied to various medical devices to enable the medical devices themselves to have anti-coagulation function.
[0031] The following description is given with reference to the accompanying drawings.
[0032] Reference Figures 1 to 3 As shown, the present invention provides an anticoagulant membrane structure, which includes a thin film substrate 1 and an anticoagulant coating 2. The anticoagulant coating 2 covers the surface of the thin film substrate 1 and has a plurality of holes 21. The plurality of holes 21 can be artificial holes or holes naturally generated during the preparation of the anticoagulant coating 2. The anticoagulant coating 2 covering the surface of the thin film substrate 1 means that the anticoagulant coating 2 can be covered on either side of the thin film substrate 1 in a single-sided manner or on both sides of the thin film substrate 1 in a double-sided manner.
[0033] Among them, the film substrate 1 is woven into a plurality of fiber bundles 12. Each fiber bundle 12 is composed of a number of fiber filaments 11. After the raw materials are made into fiber filaments 11, the plurality of fiber filaments 11 are wound to form a fiber bundle 12, and the plurality of fiber bundles 12 are further formed into a film substrate 1 through a weaving process. The film substrate 1 is a woven membrane, and its material and structural parameters (such as mesh size, fiber filament size and fiber bundle size) can be determined according to different specific application scenarios, and this application does not limit this. The fiber filaments 11 are high molecular polymers, such as PE (polyethylene), PP (polypropylene), PET (polyethylene terephthalate), polyester, polyamide, polyetheretherketone, polysulfone, natural fiber and other materials, and a combination of one or more high molecular polymers can be selected to prepare the fiber filaments 11.
[0034] The anticoagulant coating 2 is a covering attached to the surface of the film substrate 1 and has an anticoagulant function. The anticoagulant coating 2 comprises a fluoropolymer. More preferably, the anticoagulant coating 2 is composed of one or a combination of multiple fluoropolymers. Fluoropolymers such as polyvinylidene fluoride (PVDF), perfluoroethylene propylene (FEP), polyvinyl fluoride (PVF), polytetrafluoroethylene (PTFE), or other fluoropolymers with similar properties can be used to prepare the anticoagulant coating 2.
[0035] Fluoropolymers, due to the presence of fluorine groups, exhibit a high overall hydrophobicity on the surface of the anticoagulant coating 2. On one hand, the hydrophobicity of the anticoagulant coating 2 prevents blood from adhering to the surface of the film substrate 1, thereby preventing a coagulation reaction and achieving an anticoagulant effect. On the other hand, the hydrophobicity allows low-molecular-weight proteins to adsorb firmly on the coating surface, promoting the migration and crawling of endothelial cells, thereby accelerating endothelialization of the material surface and effectively reducing complications. Fluoropolymers also have excellent film-forming properties, allowing the anticoagulant coating 2 to uniformly coat the surface of the film substrate 1 and quickly solidify into a film. The film adheres firmly to the film substrate 1, resists detachment, and prevents particle shedding, resulting in excellent biosafety and stability. Fluoropolymers also have good biocompatibility and stable properties, ensuring long-term and stable anticoagulant effects. Therefore, during anticoagulant therapy, there is no need for systemic administration of antibiotics and anticoagulants, thus avoiding the side effects associated with long-term medication use. Furthermore, the presence of holes 21 in the anticoagulant coating 2 helps to increase the speed and stability of endothelialization of the material surface. In addition, the anti-coagulation coating 2 can be prepared by a relatively simple process, which is simpler to operate and uses safer materials than existing material surface modification treatments.
[0036] In practice, the anticoagulation coating 2 can be formed on the film substrate 1 by various processes such as solution dipping, ultrasonic spraying, and slit coating. Preferably, the fluoropolymer is coated on the surface of the film substrate 1 by solution dipping. The advantages of solution dipping are that the process is simple, the operation is easy, basically no toxic reagents are involved, the safety is good, and the material loss is small, and the coating effect is good. Specifically, the anticoagulation coating 2 can be formed by immersing the film substrate 1 in a solution, so that the fluoropolymer in the solution adheres to the surface of the film substrate 1. The solution is composed of a fluoropolymer and an organic solvent, and the fluoropolymer is fully dissolved in the organic solvent. The organic solvent can be selected from acetone, n-heptane, n-hexane, ethyl acetate, propyl acetate, tetrahydrofuran, dimethyl sulfoxide or other common organic solvents, and a combination of one or more organic solvents can be selected.
[0037] Specifically in this embodiment, when preparing the anticoagulation coating 2, the film substrate 1 is first immersed in a solution, and the dipping is performed at least once. The duration of each dipping is determined according to the needs. After dipping, the film substrate 1 is dried. Finally, a covering is adhered and wrapped on the surface of the film substrate 1. The covering is the anticoagulation coating 2. The anticoagulation coating 2 is evenly distributed on the surface of the film substrate 1 and has a flat surface, which is conducive to cell crawling and migration. Specifically, in the process of applying the solution to the surface of the film substrate 1 by solution dipping, the fluoropolymer can infiltrate the internal gaps 13 of the entire film substrate 1 with the help of the organic solvent, thereby forming an anticoagulation coating 2 covering the entire film substrate 1, so that the fluoropolymer can fit the surface of the entire fiber bundle 12 very well.
[0038] Furthermore, the anticoagulation coating 2 covers the surface of each fiber filament 11 and the gaps 13 (i.e., seams) between adjacent fiber filaments 11, but the anticoagulation coating 2 does not block the mesh on the film substrate 1, but exposes the mesh on the film substrate 1, thereby not affecting the performance of the film substrate 1 itself, allowing the film substrate 1 to maintain its original pore structure (i.e., mesh).
[0039] Generally, the more fluorine-containing material on the surface of the film substrate 1, the better the anticoagulant properties. However, research has found that excessive amounts of fluorine-containing material hinder cell migration and crawling on the film surface. In other words, excessive fluorine-containing material inhibits cell adhesion. Furthermore, to achieve both high anticoagulation efficiency and effective endothelialization, the thickness of the anticoagulant coating 2 is preferably 100 nm to 5000 nm. This thickness ensures the coating's anticoagulant effect while maintaining surface pores 21 and preventing obstruction of the original fiber bundles 12.
[0040] The thickness of the anticoagulant coating 2 is related to the solution concentration and the number of dipping cycles. The higher the concentration and the more dipping cycles, the thicker the resulting anticoagulant coating 2. Thus, the thickness of the anticoagulant coating 2 can be controlled by adjusting the number of dipping cycles and the solution concentration, ensuring that the thickness of the anticoagulant coating 2 is neither too thin nor too thick. A too thin thickness can reduce the anticoagulant effect, while a too thick thickness can result in the loss of surface pores 21 and obstruction of the original fiber bundles 12.
[0041] Preferably, the concentration of the solution is 0.4% to 5% (w / w). When the anticoagulant coating 2 is prepared according to the concentration of the solution, it is beneficial for the fluoropolymer to present a relatively good bridging structure at the gap 13 of the fiber filament 11, so that the anticoagulant coating 2 is connected to the surface of the fiber filament 11 through the bridging structure and covers the gap 13, making the surface of the entire anticoagulant coating 2 smoother, and at the same time, it can form holes 21 of the required pore size. It can be understood that a sunken space is formed between adjacent fiber filaments 11 (i.e., the gap 13), and the anticoagulant coating 2 builds a bridging structure on the sunken space. Preferably, the concentration of the solution is 1% to 3.5%, so that the anticoagulant effect and endothelialization promotion are both in a better state.
[0042] It should be understood that during the dip-coating process, when the solution concentration is between 0.4% and 5%, pores 21 of the desired pore size are formed in the anticoagulant coating 2 formed on the surface of the fiber filament 11. In particular, when the solution concentration is between 1% and 3.5%, the pore size and proportion of the pores 21 formed are more optimal, and the stability of endothelialization is better, while also ensuring the robustness of the coating. Preferably, at least a portion of the pores 21 are distributed on the bridging structure, which facilitates cell crawling and migration on the surface. However, a small number of pores 21 may be distributed on the surface of the fiber filament 11 outside the bridging structure. More preferably, more than 90% of the pores 21 are distributed on the bridging structure, which is more suitable for cell climbing. The pores 21 in the anticoagulant coating 2 can have a regular or irregular shape and can be the same or different sizes, and this is not limited by this application. Preferably, at least some of the pores 21 have a pore size of 0.5 μm to 5 μm, which is conducive to the migration and growth of cells such as endothelial cells and muscle cells. More preferably, pores 21 with a pore size of 2.0 μm to 5.0 μm account for more than 80% of the total number of pores, which is more suitable for cell migration and growth on the surface. The size of the pores 21 is mainly related to the solution concentration and the film-forming property of the fluorine-containing material. The higher the solution concentration, the better the film-forming property of the fluorine-containing material, then the pore size of the formed pores 21 is smaller, or even no pores 21 are formed. Further research found that when the solution concentration is 0.4% to 5%, the pore size of the pores 21 formed during the film formation process of the fluorine-containing material is basically 0.5 μm to 5.0 μm, which can meet the requirements. As the solution concentration increases, the pore size of the pores 21 will become smaller. The pore size of most pores 21 can meet the requirement of 0.5 μm to 5 μm, and is concentrated on the bridging structure (at the gap 13). In addition, a more comprehensive coating is achieved on the surface of the fiber filament 11, and its coagulation time is further prolonged, showing an excellent anti-coagulant effect.
[0043] The concentration of the solution may be 0.4%, 1%, 2%, 3.5%, 4%, or 5% or other values, and a more suitable concentration range is 1% to 3.5%. For details, see Table 1.
[0044] It should also be noted that when the solution concentration is lower than 0.4%, the anticoagulant coating 2 is difficult to completely cover the surface of the film substrate 1, and the holes 21 in the gaps 13 between the fiber filaments 11 and the fiber filaments 11 will be too large. Too large a pore size will hinder the migration and crawling of cells; when the solution concentration is higher than 5%, the holes 21 are very dense and will block the original mesh between the fiber bundles 12. The required holes 21 may not even be produced due to the excessive thickness of the coating, and the endothelialization function cannot be achieved. In addition, the coating is not firm and is easy to fall off.
[0045] It should be understood that the purpose of preparing the holes 21 on the surface of the anticoagulant coating 2 is mainly because the special surface structure of the anticoagulant coating 2 is very suitable for cell attachment, especially after the tiny holes 21 are prepared on the surface, the microporous structure is more suitable for the migration of cells such as endothelial cells and muscle cells compared to a flat surface. If the pore size is too small, it is difficult to distinguish it from a flat surface, and if the pore size is too large, it will hinder the migration and crawling process of cells. Therefore, when the anticoagulant membrane material structure of the present invention is implanted into the body as an implant, such as when the surface of a medical device is covered with the anticoagulant membrane material structure, the anticoagulant membrane material structure can prevent surface coagulation while promoting the crawling of endothelial cells on the membrane surface, thereby promoting the process of surface endothelialization and enhancing the stability of endothelialization.
[0046] Furthermore, the present invention provides a medical device equipped with the anticoagulant membrane structure provided by the present invention. The anticoagulant membrane structure can be provided on a surface (e.g., inner or outer surface) of the medical device, thereby imparting both anticoagulant and endothelialization-promoting functions to the medical device. The present invention is not limited to the type of medical device to which it can be applied, and various medical devices, such as vascular stents, left atrial occluders, and catheters, are applicable.
[0047] The advantages of the anti-coagulation membrane structure proposed in the present invention are further illustrated below with reference to experiments.
[0048] Example 1
[0049] In this embodiment, the film substrate 1 is a woven PET film. The surface of the woven PET film is dip-coated with a 1% solution to form an anti-coagulation coating 2 composed of polyvinylidene fluoride. The fluorine-containing material is polyvinylidene fluoride, and the organic solvent is acetone. After application of the anti-coagulation coating 2 composed of polyvinylidene fluoride, the surface of the woven PET film is generally flat and smooth.
[0050] like Figure 4 As shown, the anti-coagulation coating 2 forms a bridging structure (not marked) on the gaps 13 (equivalent to the sunken space) of the fiber filaments 11 . The bridging structure connects adjacent fiber filaments 11 , and a large number of holes 21 are distributed on the bridging structure.
[0051] As shown in Table 1, when 1% solution is used for dipping, the holes 21 with a pore size of 2 μm to 5 μm formed on the anti-coagulation coating 2 account for 80% of the total number of holes, and both the pore size and the proportion are relatively good. Figure 4 The pores 21 are evenly and densely distributed, varying in size, but primarily concentrated on and around the bridging structures at the gaps 13. This allows the anticoagulant coating 2 to effectively fill the gaps 13 between the fibers 11, facilitating cell proliferation, migration, and migration. Furthermore, it promotes surface endothelialization and enhances its stability, in addition to its anticoagulant properties.
[0052] Furthermore, the firmness of the anti-coagulation coating 2 and the stability of its pores 21 were verified through surface violent friction tests and fatigue tests, and the results are shown in Table 1.
[0053] The friction test method is as follows: the film containing the anticoagulant coating 2 is cleaned and cut into small pieces, fixed on the bracket, and pressed into the sheath tube, immersed in purified water to make the sheath friction multiple times (such as 5 times), and then a certain volume of water (such as 5 ml) is taken several times (such as 3 times) and the particle size and number of the particles are analyzed with a particle tester. Repeat multiple times (such as 3 times) and take the average value to measure the number of particles falling off when entering and exiting the sheath tube.
[0054] The fatigue test method is as follows: the film containing the anticoagulant coating 2 is cleaned and cut, fixed on a mold, placed in a fatigue testing machine, injected with purified water, temperature 37°C, frequency 10 Hz, amplitude ±2 mm, and fatigue test is performed for several days (such as 7 days). A certain volume of water (such as 5 ml) is taken multiple times (such as 3 times) and the particle size and number of the particles are analyzed using a particle size tester. Repeat multiple times (such as 3 times) and take the average value to measure the number of particles falling off under fatigue test conditions.
[0055] As can be seen from Table 1, when 1% solution is used for dipping, the number of particles falling off the coating surface is at a low level, which proves that the anticoagulation coating 2 at this concentration has good firmness and is not easy to fall off in complex application environments.
[0056] The anticoagulant properties of the coating were further verified through a whole blood immersion experiment. See Table 1 for specific experimental results. During the experiment, the PET woven membrane with anticoagulant coating 2 was immersed in pig venous whole blood. After 90 minutes of immersion, the surface coagulation was observed. The final measurement showed that at a solution concentration of 1%, the clotting time of the prepared PET woven membrane with anticoagulant coating 2 was approximately 30 minutes, demonstrating good anticoagulant performance. Here, clotting time refers to the time it takes for large amounts of clots to form on the surface of the coating.
[0057] Example 2
[0058] In this embodiment, the surface of the PET woven membrane is dip-coated with a 0.4% solution. Figure 5 As shown, when 0.4% solution is used for dipping, the porosity of the holes 21 in the prepared PET woven membrane with the anticoagulation coating 2 is significantly greater than that of Example 1, the pore size is also significantly increased, and the holes 21 further extend to the surface of the fiber filaments 11 (i.e., around the bridging structure). At this time, the number of holes 21 with large pores increases, and the number of holes 21 with small pores decreases, making the size distribution of the holes 21 uneven.
[0059] Referring again to Table 1, when dip-coating with a 0.4% solution, the pores 21 formed on the anticoagulant coating 2, each with a diameter of 2 to 5 μm, accounted for approximately 60% of the total number of pores. Despite the reduction in pore size and proportion, the anticoagulant coating 2 still effectively coated the PET fiber bundle, achieving the desired anticoagulation effect. Table 1 also shows that when the solution concentration was 0.4%, the number of detached particles was relatively low, demonstrating that the anticoagulant coating 2 also possesses good durability and is not easily detached in complex application environments.
[0060] In addition, the whole blood immersion experiment shows that when the solution concentration is 0.4%, the coagulation time of the prepared PET woven membrane with the anticoagulant coating 2 is about 20 minutes, and it still has a good anticoagulant effect.
[0061] However, it should be understood that the number of particles shed is positively correlated with the concentration of the dipping solution, wherein the number of particles shed in Examples 1 and 2 is at a lower level, proving that at lower concentrations, the firmness of the anticoagulation coating 2 is higher.
[0062] Example 3
[0063] In this embodiment, the surface of the PET woven membrane is dip-coated with a 2% solution. As the concentration of the solution increases, the diameter of the pores 21 becomes smaller, and the porosity also decreases accordingly.
[0064] like Figure 6 As shown, when the solution concentration is 2%, the pores 21 formed on the anticoagulation coating 2 have a significantly smaller pore size, and the number of the pores 21 increases, but the overall pore area is significantly reduced, and the pore size distribution tends to be uniform.
[0065] Continuing to refer to Table 1, when the solution concentration is 2%, the holes 21 with a pore size of 0.5μm to 2μm formed on the anticoagulant coating 2 account for about 80% of the total number of holes, and the holes 21 are mainly concentrated on the bridging structure. At the same time, a more comprehensive coating is achieved on the surface of the fiber filament 11, and its coagulation time is further extended to 45 minutes, showing a better anticoagulant performance, but the number of detached particles increases.
[0066] Example 4
[0067] In this embodiment, the surface of the PET woven membrane is dip-coated with a 5% solution, the concentration of the solution is further increased, and the pore size and porosity are further reduced.
[0068] like Figure 7 As shown, in this embodiment, the number of holes 21 on the anticoagulation coating 2 is significantly reduced compared with the above embodiment, and the pore size is also smaller, the pore size distribution is more uniform, and the holes 21 are concentrated on the bridging structure.
[0069] Continuing with Table 1, when the solution concentration was 5%, the anticoagulant coating 2 still formed pores 21 with diameters ranging from 0.5 μm to 2 μm, representing approximately 90% of the total number of pores. Furthermore, the coating thickness on the fiber filaments 11 was increased, further extending the clotting time to 55 minutes, demonstrating excellent anticoagulant efficacy.
[0070] Example 5
[0071] In this example, a 3.5% solution was dip-coated on the surface of the PET woven membrane. The test results are shown in Table 1. As can be seen, when the solution concentration was 3.5%, pores 21 with a pore size of 0.5 μm to 2 μm accounted for approximately 85% of the total number of pores, the coagulation time was 50 minutes, and the amount of particle shedding during the friction and fatigue tests was within an acceptable range, meeting the requirements.
[0072] Comparative Example 1
[0073] The surface of the PET woven membrane was dip-coated with a 0.2% solution. The test results are shown in Table 1. As can be seen, at a 0.2% solution concentration, pores 21 with a pore size of 2.0 μm to 5.0 μm only accounted for approximately 20% of the total pores, and the clotting time was 15 minutes. Although the number of particles shedding at this concentration was low, the clotting time was short, resulting in a suboptimal anticoagulant effect. Furthermore, the proportion of pores meeting the pore size requirements was low, hindering cell climbing and migration.
[0074] Comparative Example 2
[0075] The surface of the PET woven membrane was dip-coated with a 6% solution. The test results are shown in Table 1. As can be seen, at a 6% solution concentration, pores 21 with a pore size of 0.5 μm to 2.0 μm accounted for approximately 95% of the total pores, and the clotting time was 60 minutes. Although the pore size and clotting time were suitable at this concentration, significant particle shedding occurred, resulting in poor coating durability.
[0076] Comparative Example 3
[0077] A blank PET woven membrane without a polyvinylidene fluoride coating was provided for experimentation, and the test results are shown in Table 1. It can be seen that the blank PET woven membrane has a poor anticoagulant effect when it does not contain an anticoagulant coating.
[0078] Table 1. Experimental results of different solution concentrations
[0079]
[0080]
[0081] As can be seen, when the solution concentration is 0.4% to 5%, the PET woven membrane with a polyvinylidene fluoride coating exhibits good anticoagulant efficacy. Especially when the solution concentration is 1% to 3.5%, it takes into account both coating firmness and endothelialization and stability, thus achieving better results. It should also be understood that as the solution concentration increases, the pore size decreases, the coagulation time increases, but the shedding of particles increases, and the coating firmness decreases.
[0082] As should be understood from the above, the anticoagulant film material structure provided by the embodiment of the present invention has good hydrophobic properties, which can avoid blood adhesion when in contact with blood, thereby showing good anticoagulant properties. At the same time, since the fluoropolymer has good film-forming properties, the anticoagulant coating can be firmly combined with the film substrate and is not easy to fall off, thus also having good safety and stability. In addition, the hydrophobic surface of the anticoagulant coating itself is very suitable for cell attachment, which is conducive to promoting cell crawling and migration on the coating surface, thereby achieving rapid endothelialization of the material surface, thereby effectively reducing complications. In this way, when performing anticoagulant treatment, there is no need to take antibiotics and anticoagulants for a long time, avoiding a series of side effects caused by taking drugs, and the preparation of the anticoagulant coating is simpler to operate and safer in materials than the material surface modification process. It can also be applied to various medical devices, and the application scenarios are more flexible. In addition, the setting of holes on the anticoagulant coating is conducive to increasing the speed of endothelialization of the material surface and enhancing the stability of endothelialization.
[0083] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. An anticoagulant membrane structure, characterized in that: The invention comprises a film substrate woven by a plurality of fiber bundles and an anticoagulation coating containing a fluorine-containing polymer. The anticoagulation coating covers the surface of the film substrate and has a plurality of holes.
2. The anticoagulant membrane structure according to claim 1, characterized in that: The diameter of at least some of the holes is 0.5 μm to 5.0 μm.
3. The anticoagulant membrane structure according to claim 2, characterized in that: The pores with a pore size of 2.0 μm to 5.0 μm account for more than 80% of the total pores.
4. The anticoagulant membrane structure according to claim 1, characterized in that: Each fiber bundle is composed of a plurality of fiber filaments, and a sunken space is formed between adjacent fiber filaments. The anticoagulation coating forms a bridging structure on the sunken space, and at least part of the plurality of holes is distributed on the bridging structure.
5. The anticoagulant membrane structure according to claim 4, characterized in that: More than 90% of the holes are distributed on the bridging structure.
6. The anticoagulant membrane structure according to claim 1, characterized in that: Each fiber bundle is composed of a plurality of fiber filaments, the anticoagulation coating covers the surface of the fiber filaments and the gaps between adjacent fiber filaments, and the anticoagulation coating exposes the mesh on the film substrate.
7. The anticoagulant membrane structure according to claim 1, characterized in that: The thickness of the anticoagulation coating is 100nm to 5000nm.
8. The anticoagulant membrane structure according to claim 1, characterized in that: The material contained in the film substrate is one of polyethylene, polypropylene, polyethylene terephthalate, polyester, polyamide, polyetheretherketone, and natural fiber, or a combination of multiple thereof.
9. The anticoagulant membrane structure according to claim 1, characterized in that: The anticoagulation coating is composed of one or a combination of multiple fluorine-containing polymers.
10. The anticoagulant membrane structure according to claim 9, characterized in that: The anticoagulation coating is composed of a combination of one or more of polyvinylidene fluoride, polyperfluoroethylene propylene, polyvinyl fluoride and polytetrafluoroethylene.
11. A medical device, characterized in that: An anti-coagulation membrane material structure as described in any one of claims 1 to 10 is provided.